School shootings mediatized violence in a global age - Muschert, Glenn W.; Sumiala, Johanna (Bingley, U.K. : Emerald, 2012)
School shootings have raised considerable interest among scholars as a global (media) cultural phenomenon and have increased specifically in the 1990s developing into a seeming cultural epidemic. This book contributes to the current academic discussion on school shootings by analysing this phenomenon in a broader context of mediatization in contemporary social and cultural life. Mediatized logic has the power to influence us as individuals communicating about the shootings and experiencing the shootings as victimizers, victims, witnesses or bystanders. In three sections, this book explores shootings from different, yet interconnected, perspectives: a theoretical focus on media and school shootings within various sociological and cultural dimensions, specifically how contemporary media transform school shootings into mediatized violence; a focus on the practices of mediatization, with emphasis on mediated coverage of school shootings and its political, cultural, social and ethical implications; and an examination of the audiences, victims and witnesses of school shootings as well as organizations which try to manage these public crimes of significant media interest.
School shootings and cultivation analysis : on confrontational media rhetoric and the history of research on the politics of media violence / Andy Ruddock -- Media dynamics in school shootings : a socialization theory perspective / Nils Böckler, Thorsten Seeger, Peter Sitzer -- A futile game : on the prevalence and causes of misguided speculation about the role of violent video games in mass school shootings / Christopher J. Ferguson, James D. Ivory -- Media consumption in German school shooters / Rebecca Bondü, Herbert Scheithauer -- Making headlines : a quarter century of the media's characterization of Canadian school shootings / Stephanie Howells -- Analyzing visual media coverage of Amok school shootings : a novel iconographic approach / Marion G. Müller, Ognyan Seizov, Florian Wiencek -- U.S. and Finnish journalists : a comparative study of roles, responsibilities, and emotional reactions to school shootings / Klas Backholm, Marguerite Moritz, Kaj Björkqvist -- Vital explanations or harmful gossip? : Finnish journalists' reflections on reporting the interpretations of two school shootings / Jari Väliverronen, Kari Koljonen, Pentti Raittila -- Deciphering rampage : assigning blame to youth offenders in news coverage of school shootings / Glenn W. Muschert, Leah Janssen -- Media participation of school shooters and their fans : navigating between self-distinction and imitation to achieve individuation / Nathalie E. Paton -- The remote is controlled by the monster : issues of mediatized violence and school shootings / Jaclyn Schildkraut -- The mediatized victim : school shootings as distant suffering / Salli Hakala -- Collective coping through networked narratives : YouTube responses to the Virginia Tech Shooting / Simon Lindgren -- School shootings, crises of masculinities, and media spectacle : some critical perspectives / Douglas Kellner -- Afterword : is mediatization a useful concept for informing practice in journalism? / Gavin Rees -- Afterword : media and school shootings : a sociological view / Ralph W. Larkin.
Print version record
Keywords: Social Science -- Violence in Society; Social Science -- Sociology -- General; Social Science -- General; Violence in society; Society & culture: general; School shootings; Youth and violence; Violence in mass media